2018
DOI: 10.3168/jds.2017-13807
|View full text |Cite
|
Sign up to set email alerts
|

Use of a culture-independent on-farm algorithm to guide the use of selective dry-cow antibiotic therapy

Abstract: An algorithm using only computer-based records to guide selective dry-cow therapy was evaluated at a New York State dairy farm via a randomized field trial. DairyComp 305 (Valley Ag Software, Tulare, CA) and Dairy Herd Improvement Association test-day data were used to identify cows as low risk (cows that might not benefit from dry-cow antibiotics) or high risk (cows that will likely benefit). Low-risk cows were those that had all of the following: somatic cell count (SCC) ≤200,000 cells/mL at last test, an av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
90
5
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(111 citation statements)
references
References 48 publications
11
90
5
5
Order By: Relevance
“…Milk test-day SCC records and recorded mastitis incidences are useful for identifying animals for drycow treatment, as first reported by Vasquez et al (2018). Although the present study demonstrated no difference in the test-day SCS of LowSCC cows treated with teat sealant only and HighSCC cows (cows with a high SCC or an incidence of mastitis in the previous lactation; Table 3), bacteria were identified at dry-off (after animals were assigned treatment) in the quarters of 28% of HighSCC cow lactations compared with 12% of LowSCC cow lactations.…”
Section: Animal Identification For Treatment Allocationmentioning
confidence: 87%
See 2 more Smart Citations
“…Milk test-day SCC records and recorded mastitis incidences are useful for identifying animals for drycow treatment, as first reported by Vasquez et al (2018). Although the present study demonstrated no difference in the test-day SCS of LowSCC cows treated with teat sealant only and HighSCC cows (cows with a high SCC or an incidence of mastitis in the previous lactation; Table 3), bacteria were identified at dry-off (after animals were assigned treatment) in the quarters of 28% of HighSCC cow lactations compared with 12% of LowSCC cow lactations.…”
Section: Animal Identification For Treatment Allocationmentioning
confidence: 87%
“…However, the pathogens involved, as well as the timing of IMI, differ between heifers and older cows (Pyörälä and Taponen, 2009). Vasquez et al (2018) documented a numerically higher milk yield (P = 0.20) across the first 26 DIM in cows treated with teat sealant only compared with cows treated with antibiotic and teat sealant. Differences in milk yield were only detected later in lactation in the present study (Table 1).…”
Section: Milk Productionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, CNS (54.31%) were more frequent, followed by Corynebacterium spp . (12.69%), in the results of microbiological culture examinations per mammary quarter before and after delivery (42) .…”
Section: Resultsmentioning
confidence: 99%
“…Using the culture test at the end of the D-70 lactation, it has a greater number of negative teats diagnosed, using fewer antibiotics and reducing the cost of treatment in the dry period. Selective treatment at the time of drying using the culture method may be economically more viable than BDCT if the number of intramammary infections is low with lower intramammary antibiotic expense (9, 42) .…”
Section: Resultsmentioning
confidence: 99%